2020
DOI: 10.20869/auditf/2020/160/023
|View full text |Cite
|
Sign up to set email alerts
|

Emerging IT Technologies for Accounting and Auditing Practice

Abstract: The IT impact can be noticed in all activity fields of this world, and the audit is no exception from the evolution of this technological trend. Motivation: Given that professionals are progressively pursuing experimentation in working with new technologies, the development of Artificial Intelligence (AI), Blockchain, RPA, Machine Learning through the Deep Learning subset is a particularly interesting case, on which the researcher argues for debate. The objective of the article is to present the latest episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…By understanding emerging technologies, auditors will acquire new job skills such as advanced techniques in data analytics, prescriptive and prospective approaches, performance in financial audit missions and others [9]. This statement is in line with the results of Amoush's research which assumes that most auditors in Jordan use IT-based auditing to achieve better results and develop skills to use the required software.…”
Section: Resultssupporting
confidence: 54%
“…By understanding emerging technologies, auditors will acquire new job skills such as advanced techniques in data analytics, prescriptive and prospective approaches, performance in financial audit missions and others [9]. This statement is in line with the results of Amoush's research which assumes that most auditors in Jordan use IT-based auditing to achieve better results and develop skills to use the required software.…”
Section: Resultssupporting
confidence: 54%
“…Further to this, Bierstaker et al (2014) also mentioned that digital technology is a very useful tool for external auditors who can use it to perform their audit duties more efficiently, especially in a big data environment. In a more recent study, Cristea (2020) and Lee and Tajudeen (2020) observed that artificial intelligence to automate the traditional data analysis process, which includes collecting and preparing audit data, copying and transposing information between the database/software (e.g., SAP) and tools (e.g., Microsoft Excel), organising the information based on several selection criteria, integrating manual notes, and running basic tests. All of these processes have enhanced the auditing process very much, and this implies that technology advancement can facilitate auditors' performance.…”
Section: Introductionmentioning
confidence: 99%
“…In response to changes in the external environment, the management may not fully follow the goal of maximizing shareholder value and allocating high-risk, high-yield financial assets by changing the motivation of financial asset allocation to ensure the maximization of the management's interests. To understand the scientific and rationality of corporate management's decision-making, shareholders have created a series of systems such as an information disclosure system, internal control system, and company investor relationship management, to alleviate the principal-agent problem between the two [27]. At the same time, as an external supervision and governance factor, auditing can effectively transfer information between the company's shareholders and management, and further, alleviate the principal-agent problem by involving a third party in supervision.…”
Section: Convolution Neural Network-based Data Fusionmentioning
confidence: 99%